2014
DOI: 10.1371/journal.pone.0092771
|View full text |Cite
|
Sign up to set email alerts
|

Sucralose Induces Biochemical Responses in Daphnia magna

Abstract: The intense artificial sweetener sucralose has no bioconcentration properties, and no adverse acute toxic effects have been observed in standard ecotoxicity tests, suggesting negligible environmental risk. However, significant feeding and behavioural alterations have been reported in non-standard tests using aquatic crustaceans, indicating possible sublethal effects. We hypothesized that these effects are related to alterations in acetylcholinesterase (AChE) and oxidative status in the exposed animals and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 61 publications
3
20
0
Order By: Relevance
“…Whether NNS at concentrations found in breast milk exert biological effects requires further study. However, sucralose at concentrations several orders of magnitude lower than those in our samples was shown to induce oxidative stress and feeding and behavioral abnormalities in a model species of ecotoxicology (Eriksson Wiklund et al, 2014). …”
Section: Discussionmentioning
confidence: 52%
“…Whether NNS at concentrations found in breast milk exert biological effects requires further study. However, sucralose at concentrations several orders of magnitude lower than those in our samples was shown to induce oxidative stress and feeding and behavioral abnormalities in a model species of ecotoxicology (Eriksson Wiklund et al, 2014). …”
Section: Discussionmentioning
confidence: 52%
“…The wide and high consumption of SUC around the globe, have result in different scientific reports that described its occurrence in different water bodies at concentrations ranging from 0.1 to 1.0 g L −1 (Eriksson-Wiklund et al, 2014;Lange et al, 2012;Minten and Adolfsson-Erici, 2011;Loos et al, 2009), moreover this artificial sweetener poses a high stability under different conditions, which may have consequences over different aquatic species. However, the present state of knowledge is still unable to comprehend fully the possible ecotoxicological risk that this compound may pose.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioural response of Daphnia magna manifested as altered swimming height and increased swimming speed, whereas in gammarids the time to reach food and shelter was prolonged. These authors suggest that exposure to sucralose may induce neurological and oxidative mechanisms with potentially important consequences for D. magna behaviour and physiology (Eriksson-Wiklund et al, 2014). Research on the ecotoxicology of SUC is expected to increase in next years, since both short and long-term effects resulting from exposure to low levels of this compound is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chronic intake of aspartame can impair memory performance that is likely to involve increased oxidative stress and cholinergic neuronal loss . In addition to aspartame, a few in vitro and in vivo studies have indicated that exposure to saccharin or sucralose may also have detrimental effects on various cell types and tissues . When relevant studies in the literature are examined, there are no studies comparing the effects of these three artificial sweeteners on memory and neuronal survival.…”
Section: Introductionmentioning
confidence: 99%
“…[8,16,17] In addition to aspartame, a few in vitro and in vivo studies have indicated that exposure to saccharin or sucralose may also have detrimental effects on various cell types and tissues. [18][19][20][21] When relevant studies in the literature are examined, there are no studies comparing the effects of these three artificial sweeteners on memory and neuronal survival. Considering this, the present study was conducted to compare the effects of chronically given aspartame, saccharin, and sucralose on memory performance and neuronal survival and its potential relationship with oxidative stress.…”
Section: Introductionmentioning
confidence: 99%